Stereotactic body radiation therapy for the treatment of oligoprogression on androgen receptor targeted therapy in castration-resistant prostate cancer. Issue 1 (9th January 2018) - Nguyen, Thu-Cuc; Bajwa, Ravneet; Bari, Shahla; Ali, Azka; Paul Skelton, William; Federico, Roland-Austin; Bishnoi, Rohit; Wray, Justin W; Zlotecki, Robert A; Dang, Long H; Muzaffar, Jameel
Abstract: Castration-resistant prostate cancer is an incurable disease. To date, six agents-abiraterone, enzalutamide, docetaxel, cabazitaxel, radium-223 and sipuleucel-T- have shown clinical efficacy in phase III clinical trials, leading to their FDA approval. Patients are typically sequenced through most or all of these agents, and then eventually succumb to their disease. Development of new treatments remains an unmet need. We report a case of a patient who progressed on enzalutamide with a single enlarging metastatic lesion, was treated with ablative stereotactic body radiation therapy while maintaining the same systemic treatment, who then had durable complete remission. Our findings have important clinical implications and suggest novel clinical trials for this difficult to treat disease.